The Effect of Product Quality on Customer’s Satisfaction and Loyalty of EMN Brand in the Ecommerce Era - Samir, Vivi Fitriyanti; Sampurno, Sampurno; Derriawan, Derriawan (The International Journal of Business Review (The Jobs Review), 2021)
Introduction: business cosmetic has grown rapidly in the e-commerce era. In the e-commerce era, companies have the opportunity to expand their sales system to increase customer satisfaction.The purpose of study: to determine and analyze the effect of e-commerce and EMN product quality on satisfaction and its impact on consumer loyalty.Research Method: descriptive study with quantitative methods. The data was collected by distributing a survey to 155 respondents who had purchased EMN products through e-commerce sites at least once in the last six months. The survey data analysis used the SEM (Structural Equation Modeling) analysis of the SPSS 25 and AMOS 24 programs.Results: the results showed that each variable influenced each other. E-commerce has a positive effect on customer satisfaction, where the p-value = 0.014 (0.05) and the coefficient is 0.347. Product quality has a positive effect on customer satisfaction with p-value = 0.000 (0.05) and a coefficient of 0.546. Satisfaction has a significant effect on loyalty with p-value = 0.000 (0.05) and a coefficient of 0.798. Meanwhile, e-commerce has a negative effect on consumer loyalty with a p-value = 0.23 and a coefficient of -0.408. Product quality has a positive and significant effect on consumer loyalty with p-value = 0.39 and a coefficient of 0.416.Conclusion: Companies have to create attractive e-commerce site designs with complete and accurate attributes and information; companies must maintain the availability and completeness of products in e-commerce; creating a new product with a packaging design that is more attractive and of sufficiently good quality.